2020
DOI: 10.1155/2020/7636290
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Leukopoiesis in Rat Blood with Trimecaine-Based Ionic Compounds

Abstract: A study of myelostimulating activity of ionic compounds-trimecaine alkyl iodide derivatives under the cipher BIV (BIV-117, BIV-118, and BIV-119) was conducted on a model of doxorubicin pancytopenia in white laboratory rats. It was established that the compounds BIV-117 and BIV-119 had a pronounced leukopoiesis-stimulating activity, exceeding the activity of the methyluracil as a comparison drug. Compounds BIV-117 and BIV-119 had erythropoiesis- and thrombocytopoiesis-stimulating activity at the level of methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…At the same time, ionic compounds based on trimecaine have not been studied sufficiently, especially in terms of their pharmacological activity. The first reports on the leucopoiesis-stimulating and plant-growth-regulating activities of the ionic compounds based on trimecaine were published in [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, ionic compounds based on trimecaine have not been studied sufficiently, especially in terms of their pharmacological activity. The first reports on the leucopoiesis-stimulating and plant-growth-regulating activities of the ionic compounds based on trimecaine were published in [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was found that some of the compounds exhibiting mielostimulating activity [14,15] also show growth stimulating activity [16], moreover, most of these ionic compounds were found to be non-toxic towards A. Fischeri which make them promising sustainable and environmentally friendly growth stimulants. Herein we report about the synthesis and growth regulating activity of new ionic compound obtained via N-alkylation of trimecaine.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] In the present study, new ionic compounds were prepared via N-alkylation of tolperisone, diphenhydramine and trimecaine with alkyl halides (Scheme 1, Table 1). Since some of the synthesized ionic compounds have been proven to stimulate plant growth, [18,19] the ecotoxicity and myelostimulating [20] data for these substances is of great importance.…”
Section: Introductionmentioning
confidence: 99%